Association of plasma VEGF levels and the antidepressant effects of ketamine in patients with depression. (May 2021) - Zheng, Wei; Zhou, Yan-Ling; Wang, Cheng-Yu; Lan, Xiao-Feng; Zhang, Bin; Zhou, Su-Miao; Yan, Su; Yang, Ming-Zhe; Nie, Sha; Ning, Yu-Ping
Aims: Growing evidence suggests that vascular endothelial growth factor (VEGF) may be involved in the neuronal mechanisms underlying both depression aetiology and the response to ketamine treatments. The aim of this study was to examine whether changes in plasma VEGF levels are associated with the antidepressant effects of repeated ketamine infusions in patients with depression. Methods: Ninety-six patients with depression were enrolled and received six ketamine infusions during a 12-day period. Depressive symptom severity and plasma VEGF levels were measured by the Montgomery–Åsberg Depression Rating Scale (MADRS) and an enzyme-linked immunosorbent assay (ELISA) respectively, at baseline, 13 days and 26 days. Results: Despite a significant improvement in MADRS scores after patients received six ketamine infusions ( p < 0.001), no changes in plasma VEGF levels were observed at 13 days when compared with baseline. Moreover, no significant difference in plasma VEGF levels at baseline and 13 days was found between ketamine responders and nonresponders. No association was found between the antidepressant effects of repeated ketamine treatments and plasma VEGF levels. Conclusion: This study indicated that VEGF may not be a potential predictor of antidepressant response to repeated intravenous administration of ketamine in patients with depression.